2000
DOI: 10.1016/s0896-6273(00)00166-5
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Remodeling of the Retinogeniculate Synapse

Abstract: Anatomical rearrangement of retinogeniculate connections contributes to the refinement of synaptic circuits in the developing visual system, but the underlying changes in synaptic function are unclear. Here, we study such changes in mouse brain slices. Each geniculate cell receives a surprisingly large number of retinal inputs (>20) well after eye-specific zones are formed. All but one to three of these inputs are eliminated over a 3-week period spanning eye opening. Remaining inputs are strengthened approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
483
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(536 citation statements)
references
References 82 publications
(4 reference statements)
34
483
5
Order By: Relevance
“…Numerous studies have revealed developmentally regulated synaptic maturation during periods when the expression of LTP is also robust (Crair and Malenka, 1995;Rumpel et al, 1998;Chen and Regehr, 2000), and this synaptic maturation is correlated with axon remodeling during map refinement (Meyer and Smith, 2006;Ruthazer et al, 2006). Whether the experimentally induced LTP is physiologically relevant to circuit formation is unclear, however, because of the wide variety of induction protocols used and the lack of information about natural activity patterns during development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have revealed developmentally regulated synaptic maturation during periods when the expression of LTP is also robust (Crair and Malenka, 1995;Rumpel et al, 1998;Chen and Regehr, 2000), and this synaptic maturation is correlated with axon remodeling during map refinement (Meyer and Smith, 2006;Ruthazer et al, 2006). Whether the experimentally induced LTP is physiologically relevant to circuit formation is unclear, however, because of the wide variety of induction protocols used and the lack of information about natural activity patterns during development.…”
Section: Resultsmentioning
confidence: 99%
“…These results were seen during a period of significant refinement and maturation of retinogeniculate synapses, including increases in AMPA/ NMDA ratios and decreases in the presence of silent synapses (Chen and Regehr, 2000). By varying the timings of presynaptic and postsynaptic burst onsets, Butts et al (2007) also demonstrated that LTP did not depend on burst order, and that longterm depression (LTD) could be induced by separating burst onsets by hundreds to thousands of milliseconds.…”
Section: Model Of Retinal-wave-dependent Synaptic Plasticitymentioning
confidence: 93%
“…Synaptic inputs from the ipsilateral and contralateral eyes compete for territory [30][31][32][33]. To achieve mature projection patterns, synaptic remodeling occurs, including synapse elimination as well as stabilization and elaboration of remaining synapses [34,35].…”
Section: Synaptic Pruning and Neuronal Developmentmentioning
confidence: 99%
“…D uring early development in vertebrates, neurons in many parts of the nervous system form weak synapses with a large number of target cells (1)(2)(3)(4)(5)(6)(7). This early pattern of connectivity is refined through two processes: synapse elimination that removes many initial connections and synapse maturation whereby the remaining connections are strengthened (8,9).…”
mentioning
confidence: 99%